2022-LBA-931-ESGO Adipocytokines in endometrial cancer and their relationship with obesity. (27th October 2022) - Ray, Irene; Meira, Lisiane; Michael, Agnieszka; Ellis, Patricia
Abstract : Introduction: 34% of endometrial cancer can be attributed to obesity. In obese individuals, adipose tissue function deteriorates resulting in chronic inflammation and secretion of mediators called adipocytokines, which promote cancer development by cell proliferation, migration, and apoptosis inhibition. In this study, we compared the levels of adiponectin, leptin, interleukin-6 (IL-6), and tumour necrosis factor-α (TNF-α) between patients with endometrial cancer (study population) and patients without cancer with benign gynaecological disease (control population) and correlated with body mass index (BMI). In the study population, we measured the biomarker levels at different time-points (pre-hysterectomy, day 1 post-operation, and 6 months after surgery) to assess response to treatment. Methods: Adipocytokine levels were measured from plasma by ELISA in study patients (n=50) and compared with control patients (n=50) using unpaired t-test. Mixed model ANOVA was used to compare the adipocytokine levels at the three time-points in the study population and compare with the BMI. Results: Significant reduction (p<0.01) in adiponectin levels was noted between pre-operation and 6 months follow-up levels, although the differences in levels at the three time points were not significant for the other markers. Leptin levels were significantly higher in obese individuals with endometrial cancer compared to normal weight patients (p<0.05) and significantly correlated with the stage of the cancer (p<0.05). Conclusions: The reduction in plasma adiponectin levels 6 months after surgery in endometrial cancer may be due to homeostatic changes following removal of the cancer and may also be affected by radiotherapy and/or chemotherapy. The next step in the study is the evaluation of adipocytokine expression in the endometrial cancer tissue to investigate if there is a correlation with plasma levels that may impact cancer development and progression.